Optimization of freeze drying conditions for purified pectinase from mango (Mangifera indica cv. Chokanan) peel - Amid, Mehrnoush; Mustafa, Shuhaimi; Abd Manap, Mohd Yazid (MDPI, 2012)
Response surface methodology (RSM) along with central composite design (CCD) was applied to optimize the freeze drying conditions for purified pectinase from mango (Mangifera indica cv. Chokanan) peel. The effect of pectinase content (−2.66, 62.66 mg/mL), Arabic gum (−1.21, 10.21%, w/v), and maltodextrin (0.73, 7.26%, w/v) as independent variables on activity, yield, and storage stability of freeze-dried enzyme was evaluated. Storage stability of pectinase was investigated after one week at 4 °C and yield percentage of the enzyme after encapsulation was also determined. The independent variables had the most significant (p < 0.05) effect on pectinase activity and yield of the enzyme. It was observed that the interaction effect of Arabic gum and maltodextrin improved the enzymatic properties of freeze-dried pectinase. The optimal conditions for freeze-dried pectinase from mango peel were obtained using 30 mg/mL of pectinase content, 4.5 (%, w/v) of Arabic gum, and 4 (%, w/v) of maltodextrin. Under these conditions, the maximum activity (11.12 U/mL), yield (86.4%) and storage stability (84.2%) of encapsulated pectinase were achieved.